Toward Enhanced Fixation of CO2 in Aquatic Biomass: Focus on Microalgae - Gerotto, Caterina; Norici, Alessandra; Giordano, Mario (Frontiers in Energy Research, 2020)
The need to reduce the CO2 footprint of human activities calls for the utilization of new means of production and new sources of products. Microalgae are a very promising source of a large variety of products, from fuels to chemicals for multiple industrial applications (e.g., dyes, pharmaceutical products, cosmetics, food and feed, new materials for high tech manufacture), and for processes such as wastewater treatment. Algae, as photosynthetic organisms, use light to energize the synthesis of organic matter and differently from most terrestrial plants, can be cultured on land that is not used for crop production. We describe the main factors contributing to microalgae productivity in artificial cultivation systems and discuss the research areas that still need investigation in order to pave the way to the generation of photosynthetic cell factories. We shall comment on the main caveats of the possible mode of improving photosynthetic efficiency and to optimize the partitioning of fixed C to products of commercial relevance. We address the problem of the selection of the appropriate strain and of the consequences of their diverse physiology and culture conditions for a successful commercial application. Finally, we shall provide state of the art information on cell factories chassis by means of synthetic biology approaches to produce chemicals of interest.